Multidimensional patient-reported problems within two weeks of HIV diagnosis in East Africa: a multicentre observational study. - Victoria Simms; Nancy Gikaara; Grace Munene; Mackuline Atieno; Jeniffer Kataike; Clare Nsubuga; Geoffrey Banga; Eve Namisango; Suzanne Penfold; Peter Fayers; Richard A Powell; Irene J Higginson; et al. (PLoS ONE, 2013)
We aimed to determine for the first time the prevalence and severity of multidimensional problems in a population newly diagnosed with HIV at outpatient clinics in Africa.Recently diagnosed patients (within previous 14 days) were consecutively recruited at 11 HIV clinics in Kenya and Uganda. Participants completed a validated questionnaire, the African Palliative Outcome Scale (POS), with three underpinning factors. Ordinal logistic regression was used to evaluate risk factors for prevalence and severity of physical, psychological, interpersonal and existential problems.There were 438 participants (62% female, 30% with restricted physical function). The most prevalent problems were lack of help and advice (47% reported none in the previous 3 days) and difficulty sharing feelings. Patients with limited physical function reported more physical/psychological (OR = 3.22) and existential problems (OR = 1.54) but fewer interpersonal problems (OR = 0.50). All outcomes were independent of CD4 count or ART eligibility.Patients at all disease stages report widespread and burdensome multidimensional problems at HIV diagnosis. Newly diagnosed patients should receive assessment and care for these problems. Effective management of problems at diagnosis may help to remove barriers to retention in care.